"imprinted now/ into that world": Galway Kinnell's Poetics of Relationality - Lyriotakis, Ariana Michalina (Trinity College Dublin. School of English. Discipline of English, 2026)
This doctoral thesis presents a single-author study of poet Galway Kinnell (1927-2014) and the first sustained examination of his work posthumously. As a critical appraisal, it traces his creative engagement with intellectual inheritance, using it as a methodological framework by which to locate complex geographical imaginations in his literary practice. Using a two-pronged approach, the study finds its bearings in geocriticism, incorporating principles of spatial literary theory, literary and human geography, and continental philosophy. Firstly, it details how these heterogeneous relationships with inheritance—Transcendentalism and the American Renaissance; Whitmanian idioms; Iran and She'r-e Nimaa'i (New Persian Poetry); and contemporary poetic affiliation—each come to bear on the materiality and the colloquy of his work. Secondly, the project argues for the significance of the geographical imagination as both foundational to Kinnell's ethos and central to his oeuvre, contending that his poetic cosmography is underscored by material and psychogeographies in four distinct areas: marginalisation and exclusion; sensorial witness; identity; and exile. Through close readings of Kinnell's poetry, prose, and ethnographic writing across a rich array of his corpus, the chapters attend to his emergence, development, and trajectory as an ever-shifting practitioner. In the context of post-1945 US poetry, Kinnell's consonances and contradictions intertwine with uncertainty and disarticulation, expanding a late modern preoccupation with place and landscape whilst affirming his own idiolect of spatial negotiation. Relying on both newly available and critically elided primary source materials from major Kinnell archives, the thesis suggests new milieus for his role as a Cold War poet confronting an increasingly globalised and technological world.
APPROVED
Keywords: Galway Kinnell; late modernism; geographical imagination; lyric poetry; genre theory; ghazal